(untitled) (Revista de Psicología, 2019)
This paper shows the results of a research about Learning Approaches on 157 students from the Psychopedagogy and Sciences of Education courses from the School of Psychology and Education of the Pontifical Catholic University (Pontificia Universidad Católica), Buenos Aires, Argentina. The Biggs-Hernández Pina’s Study Process Questionnaire (SPQ) was used. In the group under study, the predominance of the Surface, Deep and Achieving approaches were analyzed. The analysis differentiated the students’ level in the university course (Psychopedagogy). From the conclusions, orientation activities addressed to teachers were carried out in order to optimize the action of education.